Abstract 145: Hyperacute Virtual Reality Augmented Rehabilitation (VRAR) in the Neurological ICU: A Safety and Feasibility Study - Galadu Subah; Fangyi Lin; Tiffany Ming; Kevin Clare; Akihiko Oishi; Akash Thacker; Sarah Bulbul; Anaz Uddin; Eric Feldstein; Bridget Nolan; Jose Dominguez; Sabrina Zeller; et al. (Stroke: Vascular and Interventional Neurology)
Introduction Virtual reality (VR) has shown great promise in stroke rehabilitation, providing interactive exercises that target motor and cognitive impairments with minimal adverse events and positive outcomes in improving motor function, balance, and patient motivation. However, most post‐stroke rehabilitation focuses on recovery after discharge, emphasizing the need for efficient interventions like VR to make the most of limited hospital rehab time for stroke survivors. This study aimed to evaluate the safety and feasibility of incorporating hyperacute virtual reality augmented rehabilitation (VRAR) as part of acute stroke care. Methods A prospective, proof‐of‐concept study was conducted with 13 eligible patients who experienced hemorrhagic or ischemic stroke between July 1st, 2021, and January 1st, 2022. Enrolled patients received VRAR in addition to the standard‐of‐care rehabilitation. Patients with dementia, expressive aphasia, delirium, or were unable to participate in physical therapy/ utilize the virtual reality hardware were excluded. Demographic data, functional scores, and complications were collected. Results Of the 13 patients who used the VRAR rehabilitation program, ten completed up to three visits. The cohort consisted of 50% male patients with a mean age of 73.6 years. Half of the patients had a primary diagnosis of ischemic stroke, while the rest were diagnosed with either hemorrhagic stroke (30%) or transient ischemic attack (20%). The mean length of hospital stay was 11.1 days, and the median time from admission to rehabilitation was 4 days. Most patients (80%) were discharged to outpatient rehabilitation, while 20% were discharged home. The median number of sessions was one, with four patients using the VRAR program multiple times. Despite the withdrawal of two patients (15.4%) who expressed mild discontent, there were no adverse events reported during the use of the VRAR rehabilitation program. Conclusion The findings of this study offer evidence backing the safety and feasibility of integrating VRAR as a supplementary tool in hyperacute stroke care. These results underscore the potential of VR therapy as a promising addition to conventional stroke rehabilitation methods.